Home repair - McGowan, John (Dorling Kindersley, 1991)
Designed as a "fix-it" guide, this book provides information and advice on many aspects of home repair. Also included is a guide to the tools and materials needed for each repair. Features on "points-to-remember", hints and tips on both traditional and modern techniques are also included.